Analisis Kritis Terhadap Metodologi Penulisan Rasm Ustmani dalam Konteks Sejarah Penulisan Al-Qur'an - Mastur, Ali (Ikatan Da'i Indonesia, 2025)
This study critically analyzes the metodologi penulisan rasm Utsmani as the standard for writing the Qur'an text since the era of Caliph Utsman bin Affan (Fathul Amin 2020). A qualitative descriptive method was used, including literature review and manuscript analysis, with data coded according to the kaidah rasm such as hadzf, ziyadah, hamzah, and badal. Out of 150 manuscripts, 87% consistently followed the kaidah rasm Utsmani, while the rest showed local variations. The distribution of features—hadzf (42%), ziyadah (35%), hamzah (15%), and badal (8%)—showed a significant correlation with the manuscripts' chronological periods (p < 0.05). A case study on manuscript LSM MJ 014 confirmed that the rules are maintained despite local orthographic influences. In conclusion, the rasm Utsmani is the result of a historical evolution based on the prinsip tauqifi and scholarly consensus, remaining relevant as the authentic standard. This research is vital for manuscript management, mushaf publishers, and digital technology developers. Recommendations include training and developing digital protocols based on empirical data.